Interfacial intermetallic compound layer in friction stir welded Mg/Al joints: Relationship between thickness and the welding temperature history - Xuesong Fu; Ke Chen; Qingsong Zhang; Nannan Chen; Min Wang; Xueming Hua (Journal of Magnesium and Alloys)
Thickness of the intermetallic compounds (IMC) layer at the interface has a significant effect on the mechanical properties of Mg/Al dissimilar joints. However, the thickness of IMC layer can be only obtained by metallurgical microscopy, which is destructive and has to break down the weld. Therefore, it is crucial to find a reliable approach that can non-destructively predict the thickness of IMC layer in practical application. In the current study, Mg alloy and Al alloy were friction stir butt welded (FSW) under different tool rotation speeds (TRS) to obtain different thicknesses of IMC layers. As the TRS increased from 400 rpm to 1000 rpm, thickness of the IMC layer increased from 0.4 µm to 1.3 µm, the peak welding temperatures increased from 259 °C to 402 °C, and the Z-axis downforces decreased from 10.5 kN to 3.2 kN during welding process. Higher TRS would generally induce higher welding heat input, which promotes the growth of the IMC layer and the softening of base materials. The IMC layer formed through solid-state diffusion and transformation instead of eutectic reaction according to the welding temperature history and interfacial microstructure, and its evolution process was clearly observed by plan view. In order to incorporate the effect of dramatic change of welding temperature which is the characteristic feature of FSW, PsdVoigt function was used to fit the welding temperature histories. A new prediction formula was then established to predict thicknesses of IMC layers with considering sharp welding temperature change. Predicted thicknesses gave good agreement with measured thicknesses obtained experimentally under different welding parameters, which confirmed the accuracy and reliability of the new prediction formula. Based on this prediction formula, the time period of temperature higher than 200 °C during welding was found critical for the thickening of interfacial IMC layers.